Storia e significati della Nerezza nel Sud della Tunisia: per una nuova prospettiva - Marta Scaglioni (Archivio Antropologico Mediterraneo)
After the popular uprising in Tunisia in 2011, a new debate on racial issues, ethnic minorities, and racism has emerged in the country. Until then, speaking about Blackness and racism had been blanketed by a culture of silence, and the historical phenomena of the trans-Saharan slave trade and of slavery had been relegated to a past which was considered to have no ramifications into the present. On the contrary, today’s Tunisia is a “post-colonial” and “post-slavery” society, and slavery left a profound legacy onto contemporary racial dynamics. This is particularly evident in the South of the country, where racial regimes are made by social categories which are racialized according to skin colour, origin, and social status. In this article, I will analyse the history and meanings of Blackness among a lineage whose members are racialized as Black, and whose ethnonym clearly recalls a slavery past. Analysing race in the Tunisian South as a sedimented concept which stems from contingent historical trajectories, I delineate a new perspective for the study of race in Tunisia and in North Africa at large.